Intensitas Penyakit Bercak Daun Cercospora pada Kacang Tanah (Arachis hypogaea L.) di Kampung Aimasi Prafi - Adirian Korwa; Eko Agus Martanto; Hayu Siwi Pribadi (Agrotek, 2009)
Peanut economically is important because it can be used as animal food and trade materials. Cercospora leaf spot disease is the most notorious disease in Indonesian peanut plantation, because it was able reduce 50 percent of peanut production. The aim of this research was to study intensity of Cercospora leaf spot on peanut at the Aimasi village Prafi. The result showed that : 1) Averagely, disease intensity of cercospora leaf spot on peanut at the Aimasi village Prafi reached 95,7%, and 2) Cercospora infection was able to reduce the number of leaves and shoots, while the development of plant height was simultaneous with the increase of disease intensity.